Potential role of blood dendritic cells in elicitation phase of contact hypersensitivity response – preliminary study - Lesiak, Aleksandra; Bednarski, Igor; Woźniacka, Anna; Narbutt, Joanna (Dermatology Review/Przegląd Dermatologiczny, 2016)
Introduction . In contrast to our broad knowledge about the role of dendritic cells in the sensitization phase of the contact hypersensitivity response (CHS), very little is known about their function in the effector phase. The pathophysiological mechanism of blood dendritic cells’ participation in the inflammatory response in CHS is an emerging subject of study and needs to be scrutinized. Objective . To assess the presence and type of human blood dendritic cells (BDC) – plasmacytoid DC (pDC) and myeloid DC (mDC) – at the elicitation site of CHS. Material and methods. The study group consisted of 25 healthy volunteers with a mean age of 22.3 ±6.1. Each patient before the trial was sensitized with DPCP, and after 3 weeks skin biopsies were taken from the elicitation site and were immunohistochemically stained with monoclonal mouse IgG1 antibodies against blood dendritic cell antigens (BDCA). Results . Skin biopsies were divided into two groups: group 1 where the CHS score was assessed as 0 (no reaction; n = 7) and group 2 where the CHS score was assessed as 1 (any response noted; n = 18). Compared to group 1, group 2 had a significantly lower percentage of pDC (60% vs. 15% respectively) in the inflammatory infiltrate site. We also observed that the percentage of mDC was higher in group 2 compared to group 1, although this result was not statistically significant. Conclusions . Our findings provide some data on composition of inflammatory infiltrate in the elicitation phase of CHS. We suggest that the imbalance between pDC and mDC may be a key to understanding the effector phase of CHS.